Protein and overtraining: Potential applications for free-living athletes - Lowery, L.; Forsythe, C. E. (Journal of the International Society of Sports Nutrition, 2006)
Despite a more than adequate protein intake in the general population, athletes have special needs and situations that bring it to the forefront. Overtraining is one example. Hard-training athletes are different from sedentary persons from the sub-cellular to whole-organism level. Moreover, competitive, "free-living" (less-monitored) athletes often encounter negative energy balance, sub-optimal dietary variety, injuries, endocrine exacerbations and immune depression. These factors, coupled with "two-a-day" practices and in-season demands require that protein not be dismissed as automatically adequate or worse, deleterious to health. When applying research to practice settings, one should consider methodological aspects such as population specificity and control variables such as energy balance. This review will address data pertinent to the topic of athletic protein needs, particularly from a standpoint of overtraining and soft tissue recovery. Research-driven strategies for adjusting nutrition and exercise assessments will be offered for consideration. Potentially helpful nutrition interventions for preventing and treating training complications will also be presented.